Land, Livestock and Leadership among the Ju/’hoansi San of North Western Botswana - Hitchcock, Robert K. (Anthropologica, 2022)
In Africa, indigenous peoples have had difficulties in gaining secure legal rights to land and resources. The Ju/’hoansi San of the Republic of Botswana have had to contend with governmental decisions that have not allowed groups to claim land on the basis of customary tenure or long term occupation. This article examines some of the innovative ways in which the Ju/hoansi have dealt with the issues of land and resource rights, including carrying out detailed mapping of their ancestral territories and using Botswana government policies on community-based natural resource management to their advantage in gaining greater control of land, water and wildlife resources.